KINERJA SAHAM DI SEPUTAR SEASONED EQUITY OFFERINGS (SEO) - Djaja Perdana (Akademi Akuntansi YKPN Yogyakarta, 2008)
This research aims to investigate the market reaction to seasoned equity offerings (SEO). This research was conducted at Jakarta Stock Exchange over 2000-2002 using 77 emitens based on purposive sampling. Paired sample t-test is used in testing return, abnormal return and trading volume activity surronding seasoned equity offerings (SEO) announcement (t-5 until t+5). The result of the all analysis shows that there are no significant average return, abnormal return and trading volume activity surrounding seasoned equity offerings (SEO).Keywords: Seasoned Equity Offerings, Return, Abnormal Return, Trading Volume Activity